Understanding Halal Food SMEsâ€™ Behavior Intention towards E-money - Qurniawati, Rina Sari; Nurohman, Yulfan Arif (IJIBE (International Journal of Islamic Business Ethics), 2020)
This study investigates halal food SMEs intention on use e-money. Prior to the existence of e-money, banking was a solution for small and medium enterprises (SMEs) in doing business and making transactions. Entering the era of the rise of fintech, banks are also competing in issuing their respective electronic money. Â The lack of interest in halal culinary SMEs in using electronic money, it is important for fintech companies to be able to know and understand perceptions to increase interest in re-transacting using electronic money. However, these are few studies discussed behavioral intention in this new area. Consequently, this study examined the factors that influence SMEs' intention to use e-money. A total of one hundred respondents are selected using quantitative method as sources of data collection. The questionnaires are distributed using purposive sampling method in Surakarta, Indonesia. The software used for analysis is the SPSS 20. This study concludes with conclusion and limitation.